Recommendation on an updated standardization of serum magnesium reference ranges. - Rosanoff, Andrea; West, Christina; Elin, Ronald J.; Micke, Oliver; Baniasadi, Shadi; Barbagallo, Mario; Campbell, Emily; Cheng, Fu-Chou; Costello, Rebecca B.; Gamboa-Gomez, Claudia; Guerrero-Romero, Fernando; Gletsu-Miller, Nana; et al. (European Journal of Nutrition, 2022)
Purpose: Serum magnesium is the most frequently used laboratory test for evaluating clinical magnesium status. Hypomagnesemia (low magnesium status), which is associated with many chronic diseases, is diagnosed using the serum magnesium reference range. Currently, no international consensus for a magnesemia normal range exists. Two independent groups designated 0.85 mmol/L (2.07 mg/dL; 1.7 mEq/L) as the low cut-off point defining hypomagnesemia. MaGNet discussions revealed differences in serum magnesium reference ranges used by members' hospitals and laboratories, presenting an urgent need for standardization. Methods: We gathered and compared serum magnesium reference range values from our institutions, hospitals, and colleagues worldwide. Results: Serum magnesium levels designating "hypomagnesemia" differ widely. Of 43 collected values, only 2 met 0.85 mmol/L as the low cut-off point to define hypomagnesemia. The remainder had lower cut-off values, which may underestimate hypomagnesemia diagnosis in hospital, clinical, and research assessments. Current serum magnesium reference ranges stem from "normal" populations, which unknowingly include persons with chronic latent magnesium deficit (CLMD). Serum magnesium levels of patients with CLMD fall within widely used "normal" ranges, but their magnesium status is too low for long-term health. The lower serum magnesium reference (0.85 mmol/L) proposed specifically prevents the inclusion of patients with CLMD. Conclusions: Widely varying serum magnesium reference ranges render our use of this important medical tool imprecise, minimizing impacts of low magnesium status or hypomagnesemia as a marker of disease risk. To appropriately diagnose, increase awareness of, and manage magnesium status, it is critical to standardize lower reference values for serum magnesium at 0.85 mmol/L (2.07 mg/dL; 1.7 mEq/L).